Anesthesia Management in a Child with Letterer Siwe Disease - Ebrahim Espahbodi; Anahid Maleki; Abbas Ostad Alipour; Amir Abbas Yaghooti; Alireza Tak Zare; Mehdi Sanatkar (Archives of Anesthesia and Critical Care, 2018)
letterer siwe disease is a rare disease and anesthesia management of patient with this disease is very challenging because of multiorgans involvement and poor information about anesthesia. We manage a child with this disease was refered to operating room for humerous bone fracture surgery.